Bilateral M&A Activity from the Global South - Dailami, Mansoor; Kurlat, Sergio; Lim, Jamus Jerome (2012)
This paper studies the factors associated with outbound bilateral mergers and acquisitions (M&A) activity by firms located in emerging economies. The authors document recent trends in emerging market M&A flows, which have risen dramatically over the past decade, and explore the factors that may have contributed to this rise. They find distinct patterns for M&A deals according to whether the acquisition targets are in other emerging economies or advanced countries, and that these differences can be attributed to differing theoretical motivations behind foreign direct investment. The authors also consider the implications of their model for future M&A originating in the global South, in light of the global financial crisis of 2008.